THE THEORETICAL BASIS FOR STUDYING KINESICS IN LINGUISTICS - Kendjayeva Zemfira Alimjanovna (Western European Studies, 2024)
In order to better understand non-verbal and kinesics, this article examines the language and concepts used in scientific sources. Studying non-verbal cues including posture, touch, eye contact, gestures, and facial expressions is crucial since linguistics is not just about spoken communication. Understanding nonverbal cues is crucial for analyzing cultural differences
Keywords: Eye contact; facial expressions; interaction; posture